The Level of Satisfaction with the Nursing Functions Rendered by Level IV Students of Davao Doctors College - Omran, Deborah Juliet (JPAIR Multidisciplinary Research, 2008)
This study aimed to assess the level of satisfaction with the nursing functions performed by Level IV students of Davao Doctors College, Davao City. It employed a descriptive-correlational research design involving 84 clinical instructors, 141 staff nurses, and 120 patients from Davao Doctors Hospital. Data were collected through survey instruments, and statistical techniques such as weighted mean, t-test, Pearson product-moment correlation coefficient, and stepwise regression analysis were used. Results showed that patients rated all nursing functions as satisfactory, while staff nurses found the "caregiver" function satisfactory, and clinical instructors rated the "health educator" role as moderately satisfactory. Overall, the nursing functions were rated satisfactory across all groups. Clinical instructors and patients were satisfied with the nursing functions performed by students, whereas staff nurses were moderately satisfied. A significant relationship was found between nursing functions and the level of satisfaction with these functions. The four nursing roles—planner, caregiver, health educator, and coordinator—were identified as determinants of satisfaction among respondents. The study supports the effectiveness of nursing education in preparing students for professional practice, highlighting the importance of these nursing functions in achieving quality care outcomes.